Morphometric analysis of corpus callosum in relation to brain size in fetuses of South Indian population - Ankolekar, Vrinda Hari; D Souza, Anne; Hosapatna, Mamatha; D Souza, Antony Sylvan (International Journal of Research in Medical Sciences, 2017)
Background: The corpus callosum (CC) comprises axons connecting the cortices of the two cerebral hemispheres and is the principal white matter fiber bundle in the brain Morphological characteristics of fetal corpus callosum are of value from embryologic and diagnostic points of view. Knowledge of fetal callosal size is an essential prerequisite for the study of its changes during infancy and childhood. Methods: The study included twenty four formalin fixed fetuses ranging from 25 to 40 weeks obtained from department of Anatomy, Kasturba Medical College. The measurements taken were; frontal pole to occipital pole, anterior most point to posterior most point of CC, frontal pole of brain to anterior most point of CC, occipital pole of brain to posterior most point of CC, anterior edge of splenium to superior most point of superior colliculus and thickness of body of CC. Results: Spearman’s correlation test was used to determine the correlation between different parameters. A strong positive correlation was found between the length and gestational age (r=0.69), between thickness and gestational age (r=0.4) and between length and thickness of corpus callosum (r=0.5). Conclusions: Length and thickness of corpus callosum was found to increase proportionally to gestational age but it was not statistically significant. The growth of CC was proportional to the growth of brain. The precise anatomical knowledge regarding the morphology and growth of corpus callosum will provide baseline data for the diagnosis and assessment of progression of a disease affecting it.